Perceptions about environmental services and loss of forested wetlands in Monte Gordo community, Veracruz - Marín-Muñiz, José Luis; Hernández Alarcón, María E.; Silva Rivera, Evodia; Moreno-Casasola, Patricia (Instituto de Ecología, A.C., 2016)
This study investigates the perceptions of environmental services provided by forested wetlands by inhabitants of Monte Gordo, Veracruz. Information from key informants in the community was collected through semi-structured interviews. Data were analyzed and reinforced with perceptions obtained during a pilot test, and the latter were categorized according to potentially productive population (PP) and younger students (PE). The analysis included perception and reflections between young and adult people (generational). We found that perceptions of environmental services such as considering wetlands as wildlife habitat, natural water treatment areas and using them as landfill sites varied according to groups of PP and PE as compared to the reflective level generational analysis. Key informants perceived that the major ecosystem services that wetlands provide are: foodstuff, raw materials for construction, and as a tourist attraction. The role of wetlands as sites of flooding and coastal protection was not clearly perceived. Wetland loss is perceived as a situation that has increased over time in the community, however, the situations that have caused it and the local importance varied among respondents regarding their activities. Food resources and other wetland services affect them collectively so that local initiatives are required so that they integrat the villagers, local authorities and landowners from the upland areas of the community whose activities also affect the current status of wetlands in Monte Gordo. Collective action for the common good must be strengthened.